Welfare impacts of GMO adoption along the marketing chain - Valentin, Luc (Kansas State University, 2007)
Technological changes have always been subject to numerous debates and studies to establish if and how much they benefit society. Glyphosate resistant soybean can be seen as such a technological improvement that has generated numerous studies attempting to measure the welfare gains. There are obvious gains from adopting the technology from a production efficiency standpoint, as it significantly decreases production cost and simplifies weed control management. However, with some consumers being reluctant to embrace such a change, especially in Europe, it is not obvious that overall welfare gains are positive. This study attempts to address some shortcomings perceived in recent economic literature, namely the disregard of consumers’ demand responses and the lack of analysis over time. A partial equilibrium model is created where supply and demand functions are estimated based on observed prices and quantities, the adoption rate of the new technology, and production information such as yield and harvested areas. The model developed considers 6 different regions, namely the U.S., Europe, China, Argentina, Brazil and the rest of the world, and develops for each one of them a supply function and three demand functions for soybean grain, meal and oil. Once those are calibrated, the gains for the different players in the industry are computed. The findings are that the gains are proportionally allocated to the different consumers based on the share of the demand for the specific country. Price supports in the U.S. in the early years provide, proportionally to the adoption rate, more gains to the consumers. Producers gain or lose from the technology depending on whether they have adopted it or not. Countries like the U.S. or Argentina, who were the earlier adopters, definitely see an increase in their producer surplus from the adoption of the technology. Countries such as Brazil, which have delayed adopting the technology for political reasons, have faced a significant loss due to lower prices without the benefits of enjoying a cost-saving production technology. The innovator’s gain increases over time as the adoption rate rises. From a country perspective, the U.S. is without doubt the country that has benefited the most from the technology. The main reasons are that the U.S. has the largest acreage of soybean that is grown using the Glyphosate resistant technology. The U.S. consumer base for soybean products is the largest and the monopoly is a U.S.-based company. Therefore some of the gain captured abroad by the monopoly funnels into the U.S. This study finds that, from 2002 to 2005, even if the European consumer completely stopped purchasing soybean, the U.S. as a whole would still benefit from the technology. For the earlier period 1998-2005, the study finds that if Europe had decreased its demand from 35% to 48%, there would have been a possibility for the U.S. as a whole to have been made worse off by the technology.
Keywords: GMO; Welfare; Glyphosate; Soybean; Economics, Agricultural (0503)